Reducing the volume deformation of high capacity SiOx/G/C anode toward industrial application in high energy density lithium-ion batteries. (June 2019) - Li, Ge; Li, Jin-Yi; Yue, Feng-Shu; Xu, Quan; Zuo, Tong-Tong; Yin, Ya-Xia; Guo, Yu-Guo
Abstract: SiOx -based anodes have received intensive attention with the effort on increasing the energy density of lithium-ion batteries (LIBs) for applications such as electric and hybrid electric vehicles. To ensure the security and energy density of LIBs, it is prerequisite to address the cell deformation arising from the huge volume variation of SiOx -based anodes during battery operation. We herein reported the compacted SiOx /G/C granules constructed by the interfacial adhesion between SiOx nanoparticles and thin-layer graphite under the collaborative auxiliary of binder pitch, which contributes to preserving intact conduction pathway and structure integrity of anodes during the repeated lithiation/delithiation process. The as-prepared SiOx /G/C granules deliver superior cycling stability, high initial Coulombic efficiency and good rate capability. In particular, low deformation (13.7% thickness expansion), which is comparable with that of graphite anodes, could be attained in high capacity SiOx /G/C anode (653 mA h g −1 ). The excellent properties of SiOx /G/C anodes, especially in maintaining structure integrity and lowering deformation, provide insights into the rational design of high capacity electrode materials with huge volume variation. Graphical abstract: SiO x nanoparticles are uniformly anchored on thin-layer graphite and wrapped together by amorphous carbon via an effective and facile interface adhesion strategy, which is fruitful in improving electrical conductivity, maintaining structural integrity and lowering the volume deformation of SiOx -based anodes during calendering and (de)lithiation process. The resultant SiOx /G/C anodes present superior electrochemical performance and ultralow deformation under high pressing density.Image 1 Highlights: The inherent disadvantages of SiOx -based anodes are tackled by constructing intimate interfacial connection. The multifunctional binder is developed to achieve the dispersion, agglomerant and C-coating of nanoparticles. The designed SiOx -based anode exhibits ultralow volume expansion under high pressing density. The novel strategy is fruitful in maintaining structure integrity of anodes with high volume variation.